Filhos da mãe : mediações e diálogos no processo de reconhecimento de paternidade - Sperandio, Maria Ines Vancini (2015)
This dissertation analyzes the meanings of the search for recognition of paternity and for taking on paternity constructed by Brazilian law professionals, by men who are the possible fathers and by women who are the mothers. The context of this research was the “Recognition of Paternity-DNA Project” developed by the D.A. Office (“Ministério Público”) of the state of Espírito Santo, Brazil. At the introduction we analyze the socio-historical conditions that made possible the conceptualization of the “absence of the father” as a “social problem” in the Brazilian context. This analysis is used to understand the meanings of the search for recognition of paternity as well as the meanings of paternity and maternity constructed on the interactions between participants of each procedure of that legal public policy. Through ethnographic field work, interviews with participants and consultation of the files of the “Project” we observed the intervention of patterns of moralities adopted by the professionals while they mediate the process of recognition of paternity with the institutional goal of promoting the rights of children and adolescents to that recognition and to living in a family, according to Brazilian legislation (“Estatuto da Criança e do Adolescente” - ECA). The professionals construct the meanings of responsibility of being a father and responsibility of being a mother which relate to the behaviors fathers and mothers must have towards their sons as well as to the relations fathers and mothers must have with each other in order to share the child raising duties.